30 éves a debreceni angol nyelvű orvosképzés - Erdődi, Ferenc; Matesz, Klára (Gerundium, 2019)
The 30th anniversary of the English Program at the Facult y Of Medicine. The Faculty of Medicine at the University of Debrecen celebrated the 30th anniversary of the English Program in medical education in 2017. The program was initiated in 1986 with a one-year premedical course and this training has been upheld with great successes up to now. In the 1987/88 academic year 52 students from 15 countries started their studies on the General Medicine course and eight of them graduated as medical doctor (MD) at the end of the six year training period in 1992. During the 30 years the number of the admitted and then the graduated students had increased yearly. Thus, 307 students started on the first year and 180 sixth year students received MD diploma in 2017 implying the significant development and a continuous interest in medical education in English in Debrecen. From the very beginning, the curriculum of English language programs is identical with that of the Hungarian one. Students apply for admission directly or via recruiting agents while entrance exams are conducted exclusively by the staff members of the University. The English language medical education in Debrecen has been accredited in many countries including some states in the USA. From 2000 to date other medical and health related programs such as Dentistry, Pharmacy, Physiotherapy, Public Health, Molecular Biology and Complex Rehabilitation have been started and in the last year altogether 264 students graduated in these courses including also General Medicine. Parallel to the extension of the above programs from 2007 the other faculties also started education in English. By 2017 more than 5000 foreign students from 109 countries study at the University of Debrecen. Now the Coordinating Center for International Education organizes the English programs and its duties, among many other responsibilities, include contracting with recruiting agents, organizing entrance examinations, caring for the incoming students with respect to visa, health control and insurance. The income from the tuition fees has increased during the years and now represent a significant portion of the University budget, therefore it allows the renovation and also the establishment of new facilities at the University to the benefit of students. Although the students of the English Programs have different cultural, political and religious background, they establish good relation with each other and with the students studying in Hungarian. In summary, as a result of the high standards in education in English the University of Debrecen became a well-known and important institution on the educational map of the world and our intention is to uphold and further develop this acquired status in the future.